Measuring, Monitoring and Modeling Concrete Properties An International Symposium dedicated to Professor Surendra P. Shah, Northwestern University, U.S.A. - KONSTA-GDOUTOS, MARIA S.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
This state-of-the-art volume covers the latest and future trends in measuring, monitoring and modeling the properties of cement based materials including computational and experimental micro-mechanical modeling of high-performance cementitious composites (HPFRCs), mechanical behavior and fracture of conventional and new cement based composites, advanced methods for crack detection in concrete, realistic assessment and modeling for mechanical behavior of early age concrete, autogenous shrinkage and microcracking in heterogeneous systems, quantitative image analysis for microstructural characterization of concrete, development of innovative cementitious materials, composition of concretes with special rheological properties, new concepts for the processing of repair and rehabilitation measures of concrete structures and historic building materials, bond characteristics and structural behavior of fiber reinforced plastics and hybrid fabrics, and modeling of textile reinforced concrete. This book contains 94 papers and presents the latest research work of renowned experts in the area of cement and concrete sciences.
Engineering Performance and Modeling for High-Performance Cementitious Composites -- Fracture and Deformation of Cement Based Composites -- Quantifying Damage for Early Age Concrete -- Development of Innovative Cementitious Materials -- Designing Concrete for Unconventional Properties -- Quantitative Image Analysis for Microstructural Characterization of Concrete -- Concrete Deterioration, Repair and Rehabilitation -- FRPs and Textiles in Cement Composites.
Keywords: ENGINEERING; BUILDING CONSTRUCTION; ENGINEERING; BUILDING MATERIALS